Eucalyptus globulus Mediated Green Synthesis of Environmentally Benign Metal Based Nanostructures: A Review - Muhammad Usman Sadiq; Afzal Shah; Abdul Haleem; Syed Mujtaba Shah; Iltaf Shah (Nanomaterials, 2023)
The progress in nanotechnology has effectively tackled and overcome numerous global issues, including climate change, environmental contamination, and various lethal diseases. The nanostructures being a vital part of nanotechnology have been synthesized employing different physicochemical methods. However, these methods are expensive, polluting, eco-unfriendly, and produce toxic byproducts. Green chemistry having exceptional attributes, such as cost-effectiveness, non-toxicity, higher stability, environment friendliness, ability to control size and shape, and superior performance, has emerged as a promising alternative to address the drawbacks of conventional approaches. Plant extracts are recognized as the best option for the biosynthesis of nanoparticles due to adherence to the environmentally benign route and sustainability agenda 2030 of the United Nations. In recent decades, phytosynthesized nanoparticles have gained much attention for different scientific applications. Eucalyptus globulus (blue gum) is an evergreen plant belonging to the family Myrtaceae, which is the targeted point of this review article. Herein, we mainly focus on the fabrication of nanoparticles, such as zinc oxide, copper oxide, iron oxide, lanthanum oxide, titanium dioxide, magnesium oxide, lead oxide, nickel oxide, gold, silver, and zirconium oxide, by utilizing Eucalyptus globulus extract and its essential oils. This review article aims to provide an overview of the synthesis, characterization results, and biomedical applications of nanoparticles synthesized using Eucalyptus globulus. The present study will be a better contribution to the readers and the students of environmental research.